The Impact of Social Media Advertisement Awareness on Brand Awareness, Brand Image, Brand Attitude and Brand Loyalty: A Research on University Students - SAYDAN, Reha; DÜLEK, Bulut (International Journal of Contemporary Economics and Administrative Sciences, 2019)
Due to the more effective use of social media tools and the further advancement of the internet, marketing efforts of brands have nowadays become more personal, fun, attractive and social. This study analyzes the impact of social media advertisement awareness on brand awareness, brand image, brand attitude and brand loyalty. Participants of the study consisted of 390 students currently enrolled at Van Yüzüncü Yıl University. The research model and hypothesis built for the purpose of the study were tested with structural equation modelling. Results of the analyses concluded that social media advertisement awareness has an impact on brand awareness, brand awareness has an impact on brand image, brand image has an impact on brand attitude and brand attitude has an impact on brand loyalty.